A Sociolinguistic Study of English Language Barriers and Communication - Al Dilaimy, Hazim (International Journal of Language and Literary Studies, 2024)
In the field of medicine, successful student-teacher communication that happens by receiving and exchanging information depends, to a large extent, on mutual intelligibility among participants. However, failure to reach a satisfactory degree of understanding can result in confusion, misunderstanding and bitter disappointment for both parties involved in the medical class setting. One of the goals of the current study is to analyze how the English language is used by Iraqi students in the field of medical and healthcare settings where different language barriers are expected to hinder communication and learning situations. These linguistic barriers encountered by both students and instructors often result in acute communication gaps among students of science in general and students of medical departments in particular. This paper sheds light on identifying the gaps created by the lack of successful communication between instructors and their relevant students. It also tries to find ways and solutions to overcome these problems. The current inquiry studies and analyzes how language barriers pose a serious problem related to students’ cognition in language communications from socio-cognitive and linguistic points of view within students of Nursing at Al-Maarif University College. There are some linguistic and cognitive variations among students that hinder English language proficiency and communication between students and their instructors. The study adopts different tools for conducting this paper such as collecting actual writing samples by students, observations from oral interviews and a questionnaire based mainly on medical jargon. In addition, other factors that affect student-teacher communication in terms of social, cultural, male-female differences, age and educational differences will be considered. The above-mentioned problems lead to the hypothesis that they all have some negative impacts on the communication between students and instructors that create confusion and misunderstanding of lectures delivered to students mainly in English. As a result of the lack of informative communication, teachers resort to the strategy of code-switching to Arabic to achieve a full understanding of spoken or written medical discourse.